ASPECTS REGARDING THE DIMENSIONING OF THE MAGNETIC CIRCUIT IN LOW-POWER THREE-PHASE TRANSFORMERS (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
Transformers play an essential role in the transmission and distribution of electrical energy. Transformers, whether step-up or step-down, have a major influence on transmission and distribution costs and energy quality parameters. One of the main stages in the design of a transformer is the dimensioning of the ferromagnetic core, which has an impact on no-load losses, size, and manufacturing costs. This paper presents the preliminary stage of its dimensioning, focusing on the influence that certain variables have on its dimensions and performance.
Keywords: Three-phase transformer; Magnetic circuit; No-load losses